MaMYB4, an R2R3-MYB Repressor Transcription Factor, Negatively Regulates the Biosynthesis of Anthocyanin in Banana - Deng, Gui-Ming; Zhang, Sen; Yang, Qiao-Song; Gao, Hui-Jun; Sheng, Ou; Bi, Fang-Cheng; Li, Chun-Yu; Dong, Tao; Yi, Gan-Jun; He, Wei-Di; Hu, Chun-Hua (Frontiers in Plant Science, 2021)
Anthocyanins spatiotemporally accumulate in certain tissues of particular species in the banana plant, and MYB transcription factors serve as their primary regulators. However, the precise regulatory mechanism in banana remains to be determined. Here, we report the identification and characterization of MaMYB4, a R2R3-MYB repressor transcription factor, characterized by the presence of EAR (ethylene-responsive element binding factor-associated amphiphilic repression) and TLLLFR motifs. MaMYB4 expression was induced by the accumulation of anthocyanins. Transgenic banana plants overexpressing MaMYB4 displayed a significant reduction in anthocyanin compared to wild-type. Consistent with the above results, metabolome results showed that there was a decrease in all three identified cyanidins and one delphinidin, the main anthocyanins that determine the color of banana leaves, whereas both transcriptome and RT-qPCR analysis showed that many key anthocyanin synthesis structural genes and transcription factor regulators were downregulated in MaMYB4 overexpressors. Furthermore, dual-luciferase assays showed that MaMYB4 was able to bind to the CHS, ANS, DFR, and bHLH promoters, leading to inhibition of their expression. Yeast two-hybrid analysis verified that MaMYB4 did not interact with bHLH, which ruled out the possibility that MaMYB4 could be incorporated into the MYB-bHLH-WD40 complex. Our results indicated that MaMYB4 acts as a repressor of anthocyanin biosynthesis in banana, likely due to a two-level repression mechanism that consists of reduced expression of anthocyanin synthesis structural genes and the parallel downregulation of bHLH to interfere with the proper assembly of the MYB-bHLH-WD40 activation complex. To the best of our knowledge, this is the first MYB transcription factor that regulates anthocyanin synthesis that was identified by genetic methods in bananas, which will be helpful for manipulating anthocyanin coloration in banana programs in the future.